PENGOLAHAN FOTO UDARA UAV (UNMANNED AERIAL VEHICLE) MENGGUNAKAN SOFTWARE AGISOFT METASHAPE - Noversa Yafet Pinatik; Frederik Samuel Papilaya (Indragiri Islamic University, 2024)
This research aims to explain the method of utilizing UAV (Unmanned Aerial Vehicle) for aerial data photography and processing of UAV aerial photos using Agisoft Metashape software. In this context, the author will discuss the key steps in data processing, including aerial photo preprocessing, 3D model generation, digital elevation model (DEM) extraction, orthomosaic extraction, and the provision of processing information from the aerial photo data. The research flow is structured in a series of steps, encompassing all stages performed during the research process, allowing for a clear direction of the research's progression. The final results, in the form of DEM and orthomosaic, hold significant value in mapping and geospatial analysis. This research is expected to enhance the understanding of UAV usage in surveying and mapping, enabling broader applications in various sectors. Careful supervision and control of UAV flights are highly emphasized to ensure data quality. The use of UAVs and Agisoft Metashape opens up new opportunities for accurate, efficient, and effective surveying and mapping.